An Assessment of Socio-Economic Factors on Nutritional Status in Primary School - A Cross Sectional Study in Purulia of West Bengal - Arora, Dimpal; Datta, Subrata; Sau, Soudeep Kr (International Journal of Occupational Safety and Health, 2016)
Background: Child malnutrition is one of the most vital global health problems concerning in most of the poor communities leading to high morbidity and mortality. Various studies have highlighted the relation-ship between socioeconomic status and nutrition levels of primary school children. The present study focuses on socioeconomic inequality resulting in risk of malnutrition. Objectives of the Study were to find the Impact of socio-economic factors on nutritional status in primary school children. Methods: A cross sectional survey of 281 children, aged 6-10 years were selected from remote primary school in Purulia were used in the study. the primary schools were randomly selected. The studied variables included; Age, sex of the pupils, parents’ socio-economic status and family size of selected House Holds. Interview of pupils and parents was carried out using prepared Nordic questionnaire template. Weight and height of the children were measured. and Body Mass Index (BMI) was calculated by standard method. Data was analyzed using Microsoft excel, SPSS version 8.0 .The chi-square significance of association was deter-mined at Level of significance less than 0.05. Results: The proportion of girls and boys are 55.8% and 44.2% respectively. The nutritional status of children from lower socio economic class was poor as com-pared to their counter parts came from upper socio economic class. Children with BMI <5th percentile were 30.9% in low class while in high class it was only 12.1%. Prevalence of malnutrition was 41.9% among children of family size>4 as compare to 16.4% in those of House Holds had family size<5. During comparison of the studied children with children of same age group of overall West Bengal from NNMB survey, 2002, the first group had lower BMI than the second group. Conclusion: Poverty, low literacy rate, large families, food insecurity, food safety, appears to be the important factors responsible for poor health status of children from low socioeconomic class. Efforts should be given for exploring knowledge about nutritional needs during childhood, and creating nutritional and health awareness among young rural children to ensure a better quality of life for the next generation. International Journal of Occupational Safety and Health, Vol 4 No 2 (2014) 15 – 18